Muscle ischaemia in patients with orthostatic hypotension assessed by velocity recovery cycles - Humm, Andrea Monika; Bostock, Hugh; Troller, Rebekka; Z'Graggen, Werner Josef (Journal of neurology, neurosurgery and psychiatry, 2011)
ObjectivePatients with orthostatic hypotension may experience neck pain radiating to the occipital region of the skull and the shoulders while standing (so-called coat-hanger ache). This study assessed muscle membrane potential in the trapezius muscle of patients with orthostatic hypotension and healthy subjects during head-up tilt (HUT), by measuring velocity recovery cycles (VRCs) of muscle action potentials as an indicator of muscle membrane potential.MethodsEight patients with multiple system atrophy (MSA), orthostatic hypotension and a positive history for coat-hanger pain and eight normal controls (NCs) were included in this study. Repeated VRCs were recorded from the trapezius muscle by direct muscle stimulation in the supine position and during HUT for 10 min.ResultsMuscle VRC recordings did not differ between MSA patients and NCs in the supine position. During HUT, early supernormality decreased progressively and relative refractory period increased in MSA patients whereas VRC measures remained unchanged in NCs. Ten minutes after the start of HUT, early supernormality was reduced by 44% and relative refractory period was increased by 17%.ConclusionsMuscle membranes in patients with orthostatic hypotension become progressively depolarised during standing. Membrane depolarisation is most likely the result of muscle ischaemia, related to the drop in perfusion pressure caused by orthostatic hypotension. Coat-hanger ache is most likely a consequence of this muscle ischaemia.